Making Referents Seen and Heard Across Signed and Spoken Languages: Documenting and Interpreting Cross-Modal Differences in the Use of Enactment - Vandenitte, Sébastien (Frontiers in Psychology, 2022)
Differences in language use and structures between signed and spoken languages have often been attributed to so-called language modality due to the conception that speakers use both the oral-aural channel of speech and the visual-kinesic channel of visible bodily action whereas signers only use the latter. The present paper addresses cross-modal differences in enactment, a depictive communicative strategy whereby language users imitate referents. This paper reviews comparative research on enactment in signed and spoken languages and points to methodological and theoretical shortcomings and potential solutions to tackle them. First, a broader set of causal explanations needs to be considered to interpret cross-modal differences, in particular less-studied factors of language diversity like sociolinguistic and cultural ecologies, and how they interact with each other. Predictions on the cross-modal patterns of enactment are then offered based on two different hypothetical configurations of causes. Second, cross-modal diversity in enactment is shown to be inadequately and insufficiently documented. Claims on enactment are either not supported by empirical grounds or are faced with issues of size, authenticity and diversity of the investigated samples. A good solution to make up for this gap is the development of large, directly comparable corpora from diverse signed and spoken languages, ensuring solid and quantifiable grounds to test hypotheses.